Excavations at Tel Kabri III: The 2013 to 2019 Seasons - Cline, Eric H. (Culture and history of the ancient Near East, 2023)
Tel Kabri was the center of a Canaanite polity during the first half of the second millennium BCE. This volume presents the results of the archaeological work done at the site during the years from 2013 to 2019.